Notification Using Telegram to Identify and Determine the Needs of Handling Packaging Dangerous Goods - Fahlevi, Wildansyah Reza; Lukito, Indro; Sajati, Haruno (Compiler, 2019)
Aviation requires a very high level of security and safety, so that there is no problem that can harm various parties, one of the things that must be considered is about the transportation and handling of Dangerous Goods material. Existing handling system on the flight of dangerous goods systems where outside there is still a lot of risk of handling errors until there is data inaccuracy that can harm various parties, because almost all handling done manually. In addition, the plane does not want to delay and does not want to insert dangerous goods into the plane, so to anticipate the problem conditions, built a system that performs faster, easier and accurate handling, where the system uses PHP programmer language and utilize Telegram API as media Client Server. The built tool explains how to identify packaging, calculations and documents, this tool has reliability with the ability to calculate and identify faster than the manual way with average calculations whose value is significantly different. The values obtained by manually counting which is about 175 Minutes 8 Second or equivalent to 2 Hours 55 Minutes 8 Second and counting with the system  about 94 Minutes 44 Seconds or equivalent to 1 Hour 34 Minutes 44 Seconds, then more than 46% the results are different.